(untitled) (Nigerian Journal of Technology, 2018)
Ten samples from sand bars, mouth bars and continental shelf at the Onitsha end of the River Niger were analyzed for their sedimentlogical and geochemical characteristics. The textural analysis carried out on the samples revealed that they ranged from fine to medium grained, moderately to poorly sorted, angular to sub-rounded. The percentage of sand is high compared to that of silt and clay which has a small percentage. Geochemical analysis shows that the samples are high in silica (SiO2) content, and due to the poorly sorted nature of the sediments, they were described as immature. The mean grain size ranges from 0.8 to 2.9, which corresponds to coarse-fine grain sands but averagely 2.03, which is fine grained. Standard deviation ranges from 0.28 to 1.2, which range from well sorted to poorly sorted but averagely 0.74, which is moderately sorted. The skewness ranges from -0.34 to 1.13 i.e. strongly coarse skewed to strongly fine skewed but averagely near symmetrical. The kurtosis ranges from 0.42 to 1.25 i.e. very platykurtic to leptokurtic but averagely 1.4 which is leptokurtic. The comparison between the samples(sand bar, mouth and continental shelf sediments) revealed certain distinguishing characteristics; the sand bars are better sorted compared to the continental sediments, they are also of fine grain sands, intensive weathering and texturally more mature compared to the continental shelf sediments, whereas the continental shelf is characterized by poor sorting, medium and coarse grains The mouth bar has similar characteristics with the continental shelf with grain size ranging from fine to coarse grained sands. http://dx.doi.org/10.4314/njt.v37i2.4